Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Rudin PMA p.154

Define $\phi$ as:

$$\phi(x)=|x| ,\;\;\forall x\in [-1,1] \;\; \text{and}\;\; \phi(x+2)=\phi(x)$$

Let $\delta_m=\frac{1}{2} 4^{-m}, \forall m\in\mathbb{Z}^+$ and fix $x\in\mathbb{R}$. Then, Rudin states that:

$$|\sum_{n=0}^m (\frac{3}{4})^n \frac{\phi(4^n (x+\delta_m)) - \phi(4^n x)}{\delta_m}|≧ 3^m - \sum_{n=0}^{m-1} 3^n$$

I don't understand why this inequality holds.

Please help me understand this..

Thank you in advance

share|cite|improve this question
up vote 1 down vote accepted

Just to be clear: Rudin defines $$\gamma_n = \frac{\varphi(4^n(x+\delta_m))-\varphi(4^nx)}{\delta_m}.$$ You want to show that $$\left\vert \sum_{n=0}^m \left(\frac{3}{4}\right)^n \gamma_n \right\vert \ge 3^m - \sum_{n=0}^{m-1} 3^n.$$

Did you read the sentence immediately before? It says:

When $ 0 \le n \le m$, (36) implies that $|\gamma_n| \le 4^n$. Since $|\gamma_m|=4^m$, we conclude that ...

So $$\left\vert \sum_{n=0}^m \left(\frac{3}{4}\right)^n \gamma_n \right\vert = \left\vert \pm 3^m + \sum_{n=0}^{m-1} \left(\frac{3}{4}\right)^n \gamma_n \right\vert$$ depending on whether $\gamma_m$ is positive or negative. Now you can proceed...

share|cite|improve this answer
I don't get the part $|\gamma_m|=4^m$.. Why is that? – Katlus Dec 15 '12 at 10:16
@Katlus: Take a look at (39) and the text that proceeds it. Read it carefully. – wj32 Dec 15 '12 at 10:30

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.